Analisis Kesiapan Teknologi Informasi UMKM Kota Madiun menuju Pasar Digital - Anardani, Sri; Putera, Andi Rahman; Azis, Muh Nur Luthfi; Octavian, Surya Kharisma (Jurnal Teknologi Terpadu, 2022)
The purpose of this analysis activity is to find data on the readiness of UMKM in Madiun City to enter the digital market.Â This research uses a survey-based approach carried out with a cross-section method. Research data collection is carried out simultaneously and directly on the research object. The population in this study is UMKM in the city of Madiun, with a total sample of 108 UMKM. The source of data in this study is primary data obtained through the distribution of questionnaires, where the questionnaire research instrument is designed with the integration model approach ERL (E-learning Readiness). The data analysis technique uses descriptive analysis with the readiness approach from Aydin and Tasci by measuring readiness based on four factors, namely technology, innovation, people, and self-development.Â This research concludes that the technology factor is not ready and needs a slight improvement, namely the availability of hardware for UMKM actors to support digital marketing activities. The innovation, Human Resources, and self-development factors show that they are ready but need improvement so that the digital marketing process can be carried out correctly.